Synthesis, structure, antioxidant activity, and water solubility of trolox ion conjugates - Yuliya V. Yushkova; Elena I. Chernyak; Yuriy V. Gatilov; Vladimir G. Vasil'ev; Sergey V. Morozov; Igor A. Grigor'ev (Elsevier, 2018)
The interaction of trolox with ammonia, alkylamines of different classes, and amino derivatives of heterocyclic compounds, including nitroxyl radicals and alkaloids, led to the production of ammonium salts called ion conjugates (ICs). Five ICs were characterised by X-ray diffraction. This is the first time a wide range of ICs were made from trolox with amines, and ESI-MS data demonstrated they have the potential to generate pseudomolecular [(A−B+) + H]+ ions. For all obtained trolox ICs, a significant increase (1-3 orders of magnitude) in water solubility was achieved while retaining high antioxidant activity. ICs synthesised from two biologically active fragments may be used to create polyfunctional agents with varying solubility and bioavailability. Keywords: Trolox, Amines, Ion conjugates, Antioxidants, Mass-spectrometry